Design of robust protocol to enhance QoS in mobile IPV6 environment - Hussien, Loay F.; Hassan Abdalla Hashim, Aisha; Anwar, Farhat; Mahmoud, Omer; Zakaria, Omer; Saeed, Rashid Abdelhaleem (2010)
This Supporting Quality of service (QoS) in the Internet is considered as one of the main challenges that recently got the attention of many researchers. QoS is the ability of a network element (e.g. an application, a host or a router) to provide some level of assurance for consistent network data delivery. Mobile IPv6 protocol enables a mobile node to communicate with other nodes after changing its point of attachment from one IP subnet to another without changing its IP address. However it can only provide best-effort services to all its applications. The best-effort delivery works fine with the conventional Internet applications like remote login, electronic mail and file transfer. Nevertheless, the real-time applications like video telephony or virtual conferencing require special QoS. As a result, the Internet Engineering Task Force (IETF) has proposed three main architectures to support QoS namely; IntServ, Diffserv and MPLS. However these approaches were initially designed without mobility in-mind. This paper aims to propose an efficient approach to enhance QoS in the mobile IPv6 networks. Our proposed approach was evaluated and benchmarked with the standard MIPv6 proposed by IETF. The result exhibits the proposed protocol reduced the signaling cost when it is compared with the standard protocol MIPv6.